2003
DOI: 10.5194/aab-46-445-2003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of intracellular Ca<sup>2+</sup> concentration and meat quality in pigs

Abstract: The meat quality of pigs is essentially dependent on the rate and intensity of energy metabolism after slaughter. The major cellular processes in muscle cells are regulated by the Ca 2+ concentration in the cytoplasm, stimulating different energy consuming ATPases. The most essential regulator of the Ca 2+ concentration is the sarcoplasmic reticulum (SR) with its membranes, the SR Ca 2+ ATPase (Ca 2+ pump), and the calcium release channel (CRC). Defects of one or more of these elements will be of influence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…The analysis of muscle tissue microstructure demonstrated that the studied genetic groups had a normal structure of muscle tissue and did not show any degenerative lesions. The muscles visualized a well preserved sarcomere structure, proper cell nuclei and mitochondria as well as regular cross striation giving evidence for the muscle decontraction state (KÜCHENMEISTER and KUHN 2003). A lack of degenerative changes was most likely to rise from a fact that glycolysis process proceeded properly and meat acidity increased gradually.…”
Section: Discussionmentioning
confidence: 92%
“…The analysis of muscle tissue microstructure demonstrated that the studied genetic groups had a normal structure of muscle tissue and did not show any degenerative lesions. The muscles visualized a well preserved sarcomere structure, proper cell nuclei and mitochondria as well as regular cross striation giving evidence for the muscle decontraction state (KÜCHENMEISTER and KUHN 2003). A lack of degenerative changes was most likely to rise from a fact that glycolysis process proceeded properly and meat acidity increased gradually.…”
Section: Discussionmentioning
confidence: 92%
“…The potential for hypothyroidism to reduce calpain activity may result in decreased tenderness (Marple et al, 1975;Küchenmeister and Kuhn, 2003). However, lack of differences in shear force provided evidence that glucosinolates levels in the canola meal used in this experiment did not cause negative effects on tenderness.…”
Section: Meat Qualitymentioning
confidence: 85%
“…The increase in meatiness as well as rearing conditions, nutrition, handling and slaughter related processes could affect the chemical composition of muscles, their yield, as well as the mechanism which intervenes when muscles become meat (BERRI, 2000). It is well documented that stress (feed and water deprivation, struggling, stunning and environmental conditions, like hot temperature) affects the quality of the meat, and this effect depends on both duration and intensity of the stress period (OFFER, 1991;PINGEL and KNUST, 1993;LENGERKEN et al, 1997;KÜCHENMEISTER and KUHN, 2003). Some of the technological properties of meat can be determined by the rate of glycolysis, measured directly after animal slaughter (PINGEL and KNUST, 1993).…”
Section: Introductionmentioning
confidence: 99%